Convective excitation and damping of solar-like oscillations. Issue 4 (23rd May 2020) - Zhou, Yixiao; Asplund, Martin; Collet, Remo; Joyce, Meridith
ABSTRACT: The last decade has seen a rapid development in asteroseismology thanks to the CoRoT and Kepler missions. With more detailed asteroseismic observations available, it is becoming possible to infer exactly how oscillations are driven and dissipated in solar-type stars. We have carried out three-dimensional (3D) stellar atmosphere simulations together with one-dimensional (1D) stellar structural models of key benchmark turn-off and subgiant stars to study this problem from a theoretical perspective. Mode excitation and damping rates are extracted from 3D and 1D stellar models based on analytical expressions. Mode velocity amplitudes are determined by the balance between stochastic excitation and linear damping, which then allows the estimation of the frequency of maximum oscillation power, νmax, for the first time based on ab initio and parameter-free modelling. We have made detailed comparisons between our numerical results and observational data and achieved very encouraging agreement for all of our target stars. This opens the exciting prospect of using such realistic 3D hydrodynamical stellar models to predict solar-like oscillations across the Hertzsprung–Russell diagram, thereby enabling accurate estimates of stellar properties such as mass, radius, and age.